Symposium 2: Designing Video and Audio Learning Events: an Insight Into Visual Literacy in Practice: Symposium Introduction - Asensio, Mireia (Proceedings of the International Conference on Networked Learning, 2004)
Imagine you could use a technology that could capture students’ attention that could engage them and bring to them a richer, more meaningful and more vivid learning experience. This technology would not only provide on demand access and opportunities for student interaction; but could also enhance your teaching practice to open up new ways of representing, delivering and sharing your subject discipline. Through the use of this technology you would visualise a process or show how something works, moves or performs live, without the need to rely on purely text forms. With this technology, you would enable your students to ’be there’ without the constraints of time, space and safety. The use of ‘streaming’ digital video and audio to support web-based learning resources is rapidly becoming an attractive option for many educators. The vision is clear: to move away from the static text-dominated content currently prevalent on the web towards a media-enhanced environment. Video itself can be used in many ways: ‘talking head’, interviews, video diaries, video labs, simulations, instructional sequences, ‘fly on the wall’, video help etc. However, the web is not a simple delivery medium. Through the browser video sequences can be linked to slides, text conferencing, whiteboards, video conferencing, shared applications, online assessment and third party web sites. This seamless combination of digital video with other tools offers an opportunity to move beyond the current understanding of video as a simply presentational tool.